Stress-Induced Changes of Hippocampal NMDA Receptors: Modulation by Duloxetine Treatment - Calabrese, Francesca; Guidotti, Gianluigi; Molteni, Raffaella; Racagni, Giorgio; Mancini, Michele; Riva, Marco Andrea (PloS one, 2012)
It is now well established that the glutamatergic system contributes to the pathophysiology of depression. Exposure to stress, a major precipitating factor for depression, enhances glutamate release that can contribute to structural abnormalities observed in the brain of depressed subjects. On the other hand, it has been demonstrated that NMDA antagonists, like ketamine, exert an antidepressant effect at preclinical and clinical levels. On these bases, the purpose of our study was to investigate whether chronic mild stress is associated with specific alterations of the NMDA receptor complex, in adult rats, and to establish whether concomitant antidepressant treatment could normalize such deficits. We found that chronic stress increases the expression of the obligatory GluN1 subunit, as well as of the accessory subunits GluN2A and GluN2B at transcriptional and translational levels, particularly in the ventral hippocampus. Concomitant treatment with the antidepressant duloxetine was able to normalize the increase of glutamatergic receptor subunit expression, and correct the changes in receptor phosphorylation produced by stress exposure. Our data suggest that prolonged stress, a condition that has etiologic relevance for depression, may enhance glutamate activity through post-synaptic mechanisms, by regulating NMDA receptors, and that antidepressants may in part normalize such changes. Our results provide support to the notion that antidepressants may exert their activity in the long-term also via modulation of the glutamatergic synapse.